2011
DOI: 10.3109/01677063.2011.597908
|View full text |Cite
|
Sign up to set email alerts
|

Development of Patient-Specific Neurons in Schizophrenia Using Induced Pluripotent Stem Cells

Abstract: Induced pluripotent stem cell (iPSC) technology has the potential to transform regenerative medicine. It also offers a powerful tool for establishing in vitro models of disease, in particular, for neuropsychiatric disorders where live human neurons are essentially impossible to procure. Using iPSCs derived from three schizophrenia (SZ) patients, one of whom has 22q11.2del (velocardiofacial syndrome; VCFS), the authors developed a culture system to study SZ on a molecular and cellular level. SZ iPSCs were diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 133 publications
0
86
0
3
Order By: Relevance
“…The molecular and cellular mechanisms underlying the pathogenesis of SCZD remain unknown, largely because animal models are limited for the study of SCZD. Strikingly, fibroblasts of SCZD patients carrying mutations in DISC1 or other relevant genes have been recently successfully reprogrammed into iPSCs (Brennand et al, 2011;Chiang et al, 2011;Pedrosa et al, 2011). Brennand et al succeeded in recapitulating the phenotypes of SCZD, which were previously revealed by animal studies, in neurons derived from SCZD iPSCs, thus providing a shining example for the iPSC study of polygenic diseases.…”
Section: Modeling Of Neuronal Disorders With Nscsmentioning
confidence: 99%
“…The molecular and cellular mechanisms underlying the pathogenesis of SCZD remain unknown, largely because animal models are limited for the study of SCZD. Strikingly, fibroblasts of SCZD patients carrying mutations in DISC1 or other relevant genes have been recently successfully reprogrammed into iPSCs (Brennand et al, 2011;Chiang et al, 2011;Pedrosa et al, 2011). Brennand et al succeeded in recapitulating the phenotypes of SCZD, which were previously revealed by animal studies, in neurons derived from SCZD iPSCs, thus providing a shining example for the iPSC study of polygenic diseases.…”
Section: Modeling Of Neuronal Disorders With Nscsmentioning
confidence: 99%
“…Pedrosa et al 13 identified differences in gene expression in undifferentiated iPSCs, and in day 10 and day 32 derived neurons in both cases and controls. CNVs may also be introduced with increasing passage number.…”
Section: Variability In Ipscs and Derived Neuronsmentioning
confidence: 99%
“…17 iPSCs have also been established from a schizophrenia patient with a 22q11.2 deletion, a rare deletion of moderately large effect. 13 …”
Section: Proof Of Principlementioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, disease-specific iPSCs provide new prospects for disease-related R&D by enabling screening for genes and disease processes potentially modifiable by drugs identified through in vitro screening. Consequently, iPSCs have been successfully derived from patients with NDv disorders including schizophrenia [3][4][5][6][7][8][9][10][11], Down's syndrome [12][13][14][15][16][17][18][19][20][21], autism spectrum disorders (ASDs) including fragile X, Rett and Timothy syndromes [22][23][24][25][26][27][28][29][30][31][32][33][34][35], and epilepsy [36][37][38][39], as well as NDg disorders such as Alzheimer's disease [40][41][42][43][44][45][46][47][48], Parkinson's disease [49][50][51][52]…”
Section: Ipsc-based Models Of Neurological Disordersmentioning
confidence: 99%